2017
DOI: 10.1002/ente.201600728
|View full text |Cite
|
Sign up to set email alerts
|

Water–Energy Nexus Perspectives in the Context of Photovoltaic‐Powered Decentralized Water Treatment Systems: A Tanzanian Case Study

Abstract: Water and energy are inextricably linked in today's society. This paper broadly introduces the water–energy nexus before focusing on sub‐Saharan Africa, where residents have the poorest access to both clean drinking water and electricity worldwide. Given that many of the affected people live in remote areas, new solutions are required to improve the quality of life. The potential of decentralized photovoltaic‐powered membrane filtration systems for the provision of potable water is highlighted. In particular, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 36 publications
0
11
0
Order By: Relevance
“…There was increased attention in the last decade with available studies mostly carried out in South Africa and the Northern Africa regions (50% of the literature retrieved), focusing on life cycle assessments of water supply [25,40,41], while the authors in reference [13] provided an analysis of the application of the Water-Energy Nexus in water supply in the Middle East and North Africa (MENA) region. Few studies explored the use of renewable energy sources for water supply in rural areas in Ethiopia [42], Nigeria [43], and Tanzania [44], and the adoption of solar-powered borehole pumps to replace diesel-powered pumps for water supply in refugee settings [45][46][47] Furthermore, reference [48] compared the energy demand for different water supply options in the informal water supply chain in Kisumu, Kenya. At the level of water utilities, publicly available efforts to assess energy use for water supply were available for Zambia [49].…”
Section: Literature On Energy Use For Water Supply In Africamentioning
confidence: 99%
See 1 more Smart Citation
“…There was increased attention in the last decade with available studies mostly carried out in South Africa and the Northern Africa regions (50% of the literature retrieved), focusing on life cycle assessments of water supply [25,40,41], while the authors in reference [13] provided an analysis of the application of the Water-Energy Nexus in water supply in the Middle East and North Africa (MENA) region. Few studies explored the use of renewable energy sources for water supply in rural areas in Ethiopia [42], Nigeria [43], and Tanzania [44], and the adoption of solar-powered borehole pumps to replace diesel-powered pumps for water supply in refugee settings [45][46][47] Furthermore, reference [48] compared the energy demand for different water supply options in the informal water supply chain in Kisumu, Kenya. At the level of water utilities, publicly available efforts to assess energy use for water supply were available for Zambia [49].…”
Section: Literature On Energy Use For Water Supply In Africamentioning
confidence: 99%
“…Nigeria [24] Provided an energy and operational cost optimization model for seawater desalination. South Africa [44] Demonstrated the potential of small-scale photo-voltaic powered water treatment system for brackish-water to enhance water supply in remote areas.…”
Section: Reference Description Countrymentioning
confidence: 99%
“…An additional application is the use of photovoltaic cells for water treatment. [214][215][216][217][218][219] Wang et al 219 have recently reported a hybrid photovoltaic-solar water disinfection system with a dualaxis tracking system to provide drinkable water and renewable electricity. Fig.…”
Section: Photovoltaic-chemical Couplingmentioning
confidence: 99%
“…It is estimated by the United Nations that over 330 million people in Sub-Saharan Africa are still relying on unimproved drinking water sources (unprotected wells, springs and surface water) [2]. A direct correlation exists between the availability of electricity and drinking water, with the effect of energy poverty indicating that the population living with electricity is also very likely to have access to an improved water source (and vice versa) [3]. Thus, opportunities for decentralized technologies exist for the applications where little water and energy infrastructure exists and the population density is sparse.…”
Section: Introduction 1water Scarcitymentioning
confidence: 99%
“…Recent investigations at the Plataforma Solar de Almeria indicated that vacuum-assisted air gap MD technology could reduce the SEC [10,11]. The pilot MD system for seawater desalination -which exhibited an electrical conductivity (ED) of 37-40 mS/cm -exhibited a thermal SEC of 208 kWh/m 3 and an electrical SEC of 5-20 kWh/m 3 [10]. However, the water cost was hardly comparable due to the large data variations and different applications from the literature [11].…”
Section: Introduction 1water Scarcitymentioning
confidence: 99%